"China threat" theory and its implications for China's relations with Japan and South Korea during Xi Jinping's presidency - Ferlez, Iva (2025)
As China continues to rise in both economic and military terms, the China Threat Theory has emerged predominantly in US literature. This thesis examines perceptions of China in Japan and South Korea, analyzing their bilateral relations through the lens of the China Threat Theory. The main research question asks: To what extent do Japan and South Korea perceive China as a threat, and how does that perception influence their relations with China? While the primary focus is on the presidency of Xi Jinping, earlier historical developments are also included. Constructivism serves as the theoretical foundation for addressing the research question. The methodology combines comparative case studies with historical and discourse analysis, complimenting the constructivist framework well. The thesis utilizes a range of sources, including scholarly articles, government documents, surveys, and media reports. The findings reveal that Japan and South Korea perceive China as a threat, but in different dimensions. Japan’s perception is shaped by military concerns and territorial disputes with China, while South Korea’s perception is influenced by economic dependence and historical grievances. The role of their respective alliances with the United States, as well as Japan–South Korea mutual relations, also significantly shape these perceptions. The thesis concludes that perceptions of threat are socially constructed and shaped by political and societal discourse, along with media narratives. Despite ongoing tensions, both countries show signs of cooperation with China, suggesting that such perceptions are subject to change. The thesis indicates that perceptions influence international relations and shape political and economic decision-making.